1990
DOI: 10.1039/p29900001911
|View full text |Cite
|
Sign up to set email alerts
|

Solution conformation and synthesis of a linear heptapeptide containing two dehydrophenylalanine residues separated by three L-amino acids

Abstract: A heptapeptide containing two dehydrophenylalanine residues, Boc-Gly-AzPhe-Ala-Phe-Leu-AzPhe-Ala-NH Me (Boc = t-butoxycarbonyl) has been synthesised and its solution conformation investigated using 500 MHz 'H NMR and IR spectroscopy. 'H NMR studies of the solvent accessibility of NH resonances and observation of successive N,H ++ N,+, H nuclear Overhauser effects (NOEs) suggest the presence of a significant population of folded, helical structures in CDCI,. A 5-+1 intramolecular hydrogen bonding pattern provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…21 Relatively weak NOEs (1-5%) were simultaneously observed for Leu(i) ZPhe(i+ 1) NH pairs. and pairs were seen in other helical Ll zPhe-containing oligopeptides.U· 13 This may be interpreted in two ways as suggested by Chauhan et al 11 First, their conformers involve not only a right-handed helical structure, but partly an extended structure. The two distinct conformers are considered in equilibrium of a weighted population of the two conformers, based on the intensities of the observed NOEs.…”
Section: Difference Noe Of I-6mentioning
confidence: 99%
“…21 Relatively weak NOEs (1-5%) were simultaneously observed for Leu(i) ZPhe(i+ 1) NH pairs. and pairs were seen in other helical Ll zPhe-containing oligopeptides.U· 13 This may be interpreted in two ways as suggested by Chauhan et al 11 First, their conformers involve not only a right-handed helical structure, but partly an extended structure. The two distinct conformers are considered in equilibrium of a weighted population of the two conformers, based on the intensities of the observed NOEs.…”
Section: Difference Noe Of I-6mentioning
confidence: 99%
“…It has been found that in the solid state a ∆Phe residue of the Z configuration induces β-turns in short sequences [2][3][4][5][6] and a 3 10 -helix in longer ones or peptides with more than one dehydro residue. 4,[7][8][9][10][11][12][13][14][15][16][17][18][19] Similar conformational properties of ∆ Z Phe have been observed in solution by NMR 8,11,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and CD, 18,19,[27][28][29][30][31][32][33][34][35][36]…”
Section: Introductionmentioning
confidence: 65%
“…Solution-phase methodology was used to introduce the DPhe residue in the undecapeptides as a dipeptide block by dehydration of Fmoc-aa-DL-threo--phenyl serine [aa ¼ valine or alanine in the case of (I) and aa ¼ alanine in the case of (II)] using fused sodium acetate and freshly distilled acetic anhydride as reported earlier. 26 All reactions were monitored by thin layer chromatography (TLC) on precoated silica plates in at least two different solvent systems. 26 All the couplings were followed by a 5-min reaction with acetic anhydride and 1-hydroxybenzotriazole (HOBT) in dimethylformamide/dichloromethane (DMF/DCM) to cap any unreacted amines.…”
Section: Synthesis and Characterization Of Peptidesmentioning
confidence: 99%
“…26 All reactions were monitored by thin layer chromatography (TLC) on precoated silica plates in at least two different solvent systems. 26 All the couplings were followed by a 5-min reaction with acetic anhydride and 1-hydroxybenzotriazole (HOBT) in dimethylformamide/dichloromethane (DMF/DCM) to cap any unreacted amines. Fmoc deprotection was performed with piperidine (20% in DMF).…”
Section: Synthesis and Characterization Of Peptidesmentioning
confidence: 99%